Kajian Pengeluaran Biaya Kesehatan pada Pasien Stroke: A Narrative Review - Rohmah, Syifaur (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2025)
Abstract: Stroke treatment is very expensive. The number of stroke cases increases every year. Policymakers need data regarding the amount of costs incurred for stroke treatment to develop problem-solving strategies related to the financial impact of stroke. This study aims to determine the health costs of stroke patients in Indonesia. Stroke treatment costs were taken from the Garuda Portal database and National Library e-resources using the keywords